Italian Eurasian Diplomacy: Giulio Melegari and his Work as Ambassador Between Tokyo and St. Petersburg (1896-1912) - Randazzo, Francesco (Richtmann Publishing, 2012)
One of the most painful pages in Russian history is represented by its defeat in the Russian-Japanese war of 1904-1905. From that event derive the notorious Bloody Sunday (January 1906) and the October Manifesto which forced the Tsar togive the people popular representation- Duma. An observer of these events was Giulio Melegari, son of the ex Minister ofForeign Affairs Luigi Amedeo. From Tokyo to St. Petersburg, where his carrier will end, he will be a careful witness of twopowers in the center of world history and a worthy diplomat; author of the Racconigi Agreement (1909).